2017
DOI: 10.1002/oby.21816
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high‐fat diet consumption enhances offspring susceptibility to DSS‐induced colitis in mice

Abstract: Maternal HFD consumption predisposes offspring to a higher susceptibility to develop inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…94 This phenotype was associated with increased neutrophil infiltration in the gut, paralleled with higher Ccl2 transcripts. 94 A sheep model of maternal obesity reported similar changes in the fetal gut as early as the second trimester, with increased expression of monocyte/macrophage genes TNF, IL1B, IL6, IL8, CCL2, CD68, ITGAM (encoding CD11b), and CD14 in fetal large intestine. 95 Furthermore, both mRNA and protein levels of TGF-were elevated in gut tissue obtained from offspring of obese ewes.…”
Section: Maternal Obesity and Immune Homeostasis In Nonlymphoid Tissumentioning
confidence: 96%
See 2 more Smart Citations
“…94 This phenotype was associated with increased neutrophil infiltration in the gut, paralleled with higher Ccl2 transcripts. 94 A sheep model of maternal obesity reported similar changes in the fetal gut as early as the second trimester, with increased expression of monocyte/macrophage genes TNF, IL1B, IL6, IL8, CCL2, CD68, ITGAM (encoding CD11b), and CD14 in fetal large intestine. 95 Furthermore, both mRNA and protein levels of TGF-were elevated in gut tissue obtained from offspring of obese ewes.…”
Section: Maternal Obesity and Immune Homeostasis In Nonlymphoid Tissumentioning
confidence: 96%
“…Specifically, rodent studies have reported enhanced susceptibility to DSS‐induced colitis in the offspring that was accompanied by up‐regulation of NF‐κB signaling and expression of Il1b , Il6 , and Il17 genes . This phenotype was associated with increased neutrophil infiltration in the gut, paralleled with higher Ccl2 transcripts . A sheep model of maternal obesity reported similar changes in the fetal gut as early as the second trimester, with increased expression of monocyte/macrophage genes TNF , IL1B , IL6 , IL8 , CCL2 , CD68 , ITGAM (encoding CD11b), and CD14 in fetal large intestine .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Maternal high-fat diet enhanced offspring susceptibility to DSSinduced colitis, increased inflammatory cytokine IL-1β, IL-6 and IL-17, and amplified NF-кB inflammatory signaling response in mice, which was associated with suppressed AMPK phosphorylation. 102 Interestingly, in IL-10-deficient mice, AMPK phosphorylation is elevated, which could be due to energy dysregulation associated with chronic inflammation and oxidative stress; consistently, grape seed extract enriched with polyphenolic compounds prevented inflammation, and restored AMPK activity and barrier function in these mice. 96 In summary, AMPK improves gut epithelial barrier function through promoting oxidative metabolism and suppressing inflammation.…”
Section: Ampk In Epithelial Differentiation Inflammation and Barriermentioning
confidence: 99%
“…After feeding distilled water for one week, all other mice except for the normal group received 4% (w/v) DSS solution as drinking water during the fifth week. Except for the third and fifth weeks, all mice received distilled water as drinking water for the rest of the time [16,17]. During the entire experimental duration of five weeks, the SDC-L and SDC-H groups received 2 and 4 g/kg of extract of Shuidouchi daily after the optimization of crafts.…”
Section: Animal Experimentsmentioning
confidence: 99%